Microwave safety - Video Education Australasia; Learning Zone Express (Firm) (Bendigo, Vic. : Video Education Australasia, 2007)
Ever wonder how a microwave oven actually cooks the food? The mystery is solved as Chef Jonathan Locke uses a basic microwave to explain how microwave ovens cook. He also discusses safety and cooking techniques and demonstrates easy recipes
Performer: Chef Jonathan Locke
DVD format
Keywords: Microwave cooking; Microwave ovens -- Safety measures